Melanotic neuroectodermal tumor of infancy: a case report - Vega-Peña, Claudia Patricia; Fajardo-Ortiz, Lizeth Vanessa; Parra-Sanabria, Erika Alexandra; Quintana-Muñoz, Humberto; Quintero-Canasto, Edna Margarita (Revista Facultad de Odontología Universidad de Antioquia, 2020)
Melanotic Neuroectodermal Tumor of Infancy (MNTI) is a rare neoplasm originating from neural crest cells, which generally affects pediatric patients, most frequently during the first year of life. The behavior of MNTIs is benign, locally aggressive, with a recurrence of 10-15% and eventually malignant in 6.97%. This study describes the clinical, imaging, histopathological, immunohistochemical characteristics and the management of MNTI in a 5-month-old girl, whose lesion was resected and monitored. The present case illustrates the benefits of multidisciplinary integration for a correct diagnosis to ensure adequate therapeutic management, in addition to providing a report on this rare and understudied pathology.